Identification of human immunodeficiency virus envelope gene sequences influencing viral entry into CD4-positive HeLa cells, T-leukemia cells, and macrophages. - Chesebro, B (1991)
Infectious recombinant viruses were constructed from three molecularly cloned human immunodeficiency virus (HIV) strains varying in cell tropism. All recombinants showed a high infectivity titer on phytohemagglutinin-stimulated normal T lymphocytes. However, a 120-bp region of the envelope gene including the area of the V3 hypervariable loop was found to influence infectivity titer on both clone 1022 CD4-positive HeLa cells and CD4-positive CEM leukemia cells. Infectivity for macrophages was more complex. All viruses replicated in macrophages to a low level, but viral sequences both inside and outside the V3 loop region influenced the efficiency of replication. Two experiments showed that the mechanism of restriction of infection of 1022 cells by HIV strain JR-CSF was related to lack of virus entry. First, productive virus infection occurred after transfection of 1022 cells with viral plasmid DNA. Second, the nonpermissive HIV strain JR-CSF could infect 1022 cells when pseudotyped with the envelope of other retroviruses, including human T-cell leukemia virus type I (HTLV-I), HTLV-II, and amphotropic murine leukemia virus. These results demonstrate the possibility that unexpected cell types might be infected with HIV in human patients coinfected with HIV and HTLV-I or HTLV-II.